How brand attitude, brand quality, and brand value affect Thai canned tuna consumer brand loyalty - Pichit Chuenban; Puris Sornsaruht; Paitoon Pimdee (My University, 2021)
As one of the world's most valuable fish, Tuna can either be found in inexpensive tins on grocery store shelves or on high-end auction blocks destined for Japanese sashimi and sushi restaurants. Moreover, Thailand is reported to be the world's largest exporter of prepared or preserved tuna, which in 2019 contributed an estimated $2.5 billion to Thailand's exports. However, brand research is very limited for canned tuna, especially when it comes to product packaging cues, and how packaging affects a consumer's decision-making process. Therefore, this study set out to investigate which factors play the greatest role in a Thai consumer's brand loyalty (BL) for tuna fish canned products. Research teams using systematic random sampling were dispatched to five supermarkets within the Bangkok metropolitan area and collected 400 questionnaires answering items related to brand attitudes (BA), brand quality (BQ), and brand value (BV) as they related to canned tuna brand loyalty (BL). Thereafter, data analysis of the four constructs and 13 observed variables was conducted with use of LISREL 9.1, which included a confirmatory factor analysis (CFA), a goodness-of-fit (GOF) analysis along with the study's structural equation modeling (SEM). Results determined that there was a positive effect (73% R2) between all the causal factors on Thai canned tuna BL. Furthermore, the factors affecting BL ranked from the greatest to the lowest were BA, BQ, and BV with total effect (TE) values of 0.85, 0.33, and 0.19, respectively. Key takeaways from the study's research seem to indicate that canned tuna is viewed by most consumers as a 'commodity', with product availability and convenience being of the utmost importance in product brand selection. Global fishing stocks sustainability, labor costs/practices, and dolphin free catches within the tuna industry were also determined to be important aspects within the international consumer community. Also, due to the demand for high-quality and safe tuna products, adding value has become increasingly important in satisfying consumer demands and represents an opportunity for marketplace expansion.
Keywords: Skipjack tuna; LISREL; Brand Loyalty; Innovation and Socioeconomic Development